2020
DOI: 10.1007/s00190-020-01400-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving solar radiation pressure modeling for GLONASS satellites

Abstract: The Russian Global Navigation Satellite System (GLONASS) satellites have a stretched body shape and take a specific attitude mode inside the eclipse. Based on previous studies, the new Empirical CODE orbit model (ECOM2) performs better than the classical ECOM model if a satellite has elongated shape or does not maintain yaw-steering mode, and the use of an a priori box-wing (BW) model improves the orbits significantly when employing the ECOM model. However, we find that the ECOM model performs better than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Recently, Sidorov et al (2020) identified that TR force due to the emitted heat from the thermal radiator caused by the onboard atomic clock generated the orbit errors in eclipse seasons for Galileo satellites. Moreover, based on the analysis of Y 0 of ECOM1 model, the potential radiators on the −X surface were identified for GLONASS satellites (Duan et al, 2020). Wang et al (2019c) also introduced a periodic acceleration along +X direction to compensate TRP for BDS satellites, particularly for C13.…”
Section: Thermal Radiation Pressurementioning
confidence: 99%
“…Recently, Sidorov et al (2020) identified that TR force due to the emitted heat from the thermal radiator caused by the onboard atomic clock generated the orbit errors in eclipse seasons for Galileo satellites. Moreover, based on the analysis of Y 0 of ECOM1 model, the potential radiators on the −X surface were identified for GLONASS satellites (Duan et al, 2020). Wang et al (2019c) also introduced a periodic acceleration along +X direction to compensate TRP for BDS satellites, particularly for C13.…”
Section: Thermal Radiation Pressurementioning
confidence: 99%
“…Optical parameters + and are adjusted in + X and ± Z surfaces for each satellite (Duan et al 2019b). The solar panel parameter is estimated to compensate for the thermal radiation performed on solar panels (Duan et al 2020). A rotation lag of solar panels is estimated for each satellite (Rodriguez-Solano et al 2012a).…”
Section: Enhanced Box-wing Modelmentioning
confidence: 99%
“…Then, we show the impact of all the discussed physical effects on SRP. Third, we adjust all the box-wing parameters, including additional physical parameters, such as yaw bias, radiator emission and thermal radiation (Duan et al 2020(Duan et al , 2019bRodriguez-Solano et al 2012a). In addition, the GSPM parameters are determined as well by using the same GPS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Optical and infrared properties of each Sentinel-3 satellite surface are given by Montenbruck et al (2018). With this detailed information, solar radiation pressure (SRP) can be described by a box-wing macro model, as shown for one plane (Duan et al 2020), where acc represents the acceleration, A the surface area, M the total mass of the satellite, S 0 the solar flux, c the vacuum velocity of light, the thermal re-radiation factor (0 for solar panels and 1 for satellite body surfaces in this contribution), , , the fractions of absorbed, diffusely scattered, and specularly reflected photons. Furthermore, D denotes the Sun direction, N the surface normal vector, and the angle between both vectors.…”
Section: Applications In Sentinel-3 Satellite Podmentioning
confidence: 99%